Effect of Topical 5-Fluorouracil Alone versus Its Combination with Erbium:YAG (2940 nm) Laser in Treatment of Vitiligo - Abdelwahab M; Salah M; Samy N; Rabie A; Farrag A (Dove Medical Press, 2020)
Mahetab Abdelwahab,1 Manal Salah,2 Nevien Samy,2 Ahmad Rabie,1 Abdelrazik Farrag3 1Department of Dermatology and Venereology, Medical Division, National Research Centre, Cairo, Egypt; 2Department of Medical Applications of Lasers (MAL), National Institute of Laser Enhanced Sciences, Cairo University, Giza, Egypt; 3Department of Pathology, Medical Division, National Research Centre, Cairo, EgyptCorrespondence: Mahetab Abdelwahab Tel +20 101 465 7840Email mahysmr@gmail.comPurpose: To compare the efficacy of topical 5-FU as monotherapy to combined therapy of topical 5-FU and Er:YAG (2940 nm) laser in the treatment of non-segmental vitiligo (NSV).Methods: This is a prospective randomized comparative study. Thirty patients diagnosed with NSV were recruited from the dermatology outpatient clinics of the Medical Research Centre of Excellence, the National Research Centre and the National Institute of Laser Enhanced Sciences. Our study group was divided into two subgroups, Group 1 was subjected to ablative Er:YAG and 5-FU cream and Group 2 applied topical 5-FU cream. Three treatment sessions were repeated every 4 to 6 weeks and patients were followed up to 9 months. Repigmentation was assessed by digital photography and subsequent computer based image analysis.Results: Repigmentation of Group 1 patients ranged from 0 to 70% (mean 12± 7%) whilst in Group 2 this ranged from 0 to 5% (mean 1.4± 0.8%). In Group 1 repigmentation was mild in 22/30 (73.3%) and moderate to severe in 3/30 (10%) starting after 3 months and persisted or increased during the period of follow up to 9 months. Groups 1 and 2 were subdivided into A and B, vitiligo involving non-resistant and resistant areas respectively. Group 1A showed more repigmentation (mean 13.8± 8.5%) than Group 1B (mean 9.8± 4.5%) and Group 2A showed more repigmentation (mean 1.5± 1%) than Group 2B (mean 1.3± 0.5%).Conclusion: The combination of Er:YAG with 5-FU is safe and effective in treating and improving outcome in vitiligo especially of non-resistant areas. Computer based image analysis of vitiliginous lesions and assessing post-therapy response is an easy, quick, and reliable method.Keywords: 5-fluorouracil, ablative, Er:YAG, vitiligo, image analysis, resistant